Cross-national risk factors for childbirth-related PTSD: Findings from the INTERSECT study - Handelzalts, Jonathan E; Ayers, Susan; Webb, Rebecca; Constantinou, Georgina; Lucas, Grace; Grollman, Christopher; Ohayon, Shay; Awad Sirhan, Natalia; Baird, Kathleen; Baldisserotto, Márcia; Batool, Ramish; Batool, Shahida; et al. (My University, 2025)
Childbirth-related post-traumatic stress disorder (CB-PTSD) is an underrecognized condition with consequences for mothers and infants. This study aimed to determine risk factors for CB-PTSD symptoms across countries within a stress-diathesis framework, focusing on antenatal, birth-related, and postpartum predictors.
Keywords: Childbirth; Postpartum; Risk Factors; PTSD